Asesoría y seguimiento para los rectores de las (54) cincuenta y cuatro instituciones educativas del departamento del Quindío, en el manejo presupuestal de contabilidad del fondo de servicios educativos (2013)
According to Government figures around a million children aged 5 to 16 years abandoned the education system in recent years, being forced to enter the workforce early. Therefore, in compliance with the existing legal and Constitutional Court who made it clear that fundamental rights are an essential core that is to meet the basic needs of their owners and therefore can not be restricted or by government actions or either by individuals, of the national government unexpectedly slashed finished with tuition and financial contributions, giving rise to such important aspects as gratuity, coverage, quality and efficiency, all while attempting to somehow strengthen the inclusion and permanence of children in the classroom.